Analisis Pengaruh Penggunaan Internet Terhadap Minat Belajar Mahasiswa (Studi Kasus:Perguruan Tinggi di Kota Palembang) - Desi Pibriana; Desy Iba Ricoida (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Information Technology in higher education are expected to be used to improve the quality of student in learning, such as facilitating student to access the Internet easily by making it easy to get the information from online sites. However, Internet is often misused by student, they are using it to access social media and gamesinstead of support their learning process. Based on this fact, we need to evaluate how Internet usage can affect students learning interest and behavior in Palembang by using the concept of Theory Reasoned Action (TRA) Model. Structural Equation Modeling (SEM) with software AMOS 22 is used to analyze this problem. The result of this study show that the subjective norm have no effect on student interest on learning while Internet Usage behavior has. Based on this result, it can provide an input for universities to maximize Internet usage to support student interest on learning